A newsreel history of the Third Reich: Volume 05 [videorecording (DVD)] : assault on the Mediterranean. (Artsmagic, 2006)
"Includes unique footage plundered by Russian Troops in 1945. Compiled as it is from German newsreels which were made under the influence of Goebbels' ministry of propaganda, these are by no means accurate histories but allow unique insight into how the period leading up to and including WW2 was presented to the German people. Volume 5 deals with the first part of the year 1941. It covers amongst other topics the shelling of Dover from the French coast; the capitulation of Yugoslavia; Hitler in the Balkans; advances in Greece; the paratroop invasion of Crete; General Rommel's desert army in Cyrenacia advancing towards Torbruk and Solum and Hitler's visits to southern Styria."--Container.